Uma tipologia do anúncio publicitário = A tipology of advertising - Rosa, António Machuco (2019)
In this paper we propose a classification of the main types of commercials, usingas guide some crucial moments of the history of the publicity. The two main typesof ads were identified by J. Walter Thompson in the early twentieth century. On theone hand advertising reason-why and, on the other hand, a type of advertisementthat consists of the desire that the advertisement communicates to the viewer andthat it aims to display to third parties. The Lux soap campaign will serve as anexample. We then show how the concept of Unique Selling Proposition is adevelopment of reason-why advertising. We also analyse a third type of ads thatcan incorporate either reason-why elements or elements associated with desire.These are ads run by celebrities. We then look at two additional types of ads. Onthe one hand the anti-publicity publicity created by Bill Bernbach and, on the otherhand, the anti-celebrities ads, which criticize the use of celebrities in publicity.These latter two types convey the idea of an autonomous individual and theystrategically use utility, reason-why arguments, to convey a higher form of desire.